Pengaruh Model Pembelajaran Think Talk Write terhadap Peningkatan Kemampuan Kognitif Siswa Kelas X pada Subkonsep Pencemaran Lingkungan - Dewi, Nela; Desy Prasethyaning Thiyas (Lembaga Penelitian dan Pengabdian kepada Masyarakat of Universitas Islam Negeri Jurai Siwo Lampung, 2025)
In the field of education, educators often do not fully understand the extent of their students’ knowledge. As a result, the importance of students' cognitive abilities is frequently overlooked, even though these abilities can serve as a benchmark for improving the quality of education. The use of an appropriate learning model can be an alternative strategy to achieve learning success. This study aims to determine the effect of the Think-Talk-Write (TTW) learning model on students' cognitive abilities in natural science subjects. The TTW model is a learning strategy designed to encourage students to think critically, discuss their ideas verbally, and write down their thoughts based on the cognitive processes they have undergone. The research method used in this study was quasi-experimental. The sample was determined using a purposive sampling technique, selecting class X.1 as the experimental class and class X.2 as the control class. The population in this study consisted of all Grade X students at Muhammadiyah High School in Serang City. Data collection techniques included tests (in the form of multiple-choice questions) and non-test instruments (in the form of learning implementation observation sheets). Data were analyzed using descriptive statistical techniques, including validity tests, reliability tests, normality tests, homogeneity tests, and hypothesis testing with the assistance of SPSS version 25. The results of the independent sample t-test showed a significance value of 0.012, which is less than the significance level α = 0.05. Therefore, H1 is accepted and H0 is rejected, indicating that the Think-Talk-Write (TTW) learning model has a significant effect on students' cognitive abilities.